In vitro Seed Germination, Protocorm Formation and Plantlet Regeneration in Aerides ringens Fisher (Plant Tissue Culture and Biotechnology, 2019)
An attempt was made to in vitro seed germination and plantlet regeneration in Aerides ringens, a threatened, endemic and epiphytic orchid. Five basal media Knudson C (KC), Vacin and Went (VW), Burgeff’s (N3f), half strength MS, MS were examined for their effectiveness. Germination occurred in all the media. However, KC medium proved to be the best for seed germination (70.8%) and half strength MS was superior for the differentiation of protocorm like bodies (PLBs) into seedlings. The seeds were also cultured on various plant growth regulators (PGRs) to evaluate their effectiveness on seed germination and further differentiation. Among the PGRs tested, 0.57 μM IAA (IAA 89.3%), 4.64 μM Kn (88.6%) and 2.21 μM BAP (90.7%) and 0.57 μM IAA + 0.55 μM BAP (96.5%) were stimulated the germination and further differentiation of PLBs into seedlings. The concentrations of 2.21 μM BAP and combination of 0.57 μM IAA + 0.55 μM BAP stimulated the formation of MPLBs, which later differentiated into shoots and roots. Four potting substrates were evaluated for Ex vitro seedling survivability of which brick: charcoal: decaying litter: coconut husk (1 : 1 : 1 : 1) gave maximum survival rate (89.0%).Plant Tissue Cult. & Biotech. 29(1): 49-62, 2019 (June)